2015
DOI: 10.1111/jgs.13830
|View full text |Cite
|
Sign up to set email alerts
|

Methylomic Aging as a Window onto the Influence of Lifestyle: Tobacco and Alcohol Use Alter the Rate of Biological Aging

Abstract: Objectives To examine the effect of the relationship between alcohol and cigarette consumption on biological aging using deoxyribonucleic acid (DNA) methylation-based indices. Design We examined the association between DNA methylation indices of smoking and alcohol to those for biological aging in two independent cohorts using the epigenetic “clock” provided by Hannum and colleagues. Setting Longitudinal studies of aging and the effect of psychosocial stress. Participants Publicly available genome-wide m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 35 publications
(87 reference statements)
5
62
0
1
Order By: Relevance
“…However, none of the genomic regions that become either hypermethylated or hypomethylated with aging has been identified in smoking EWASs [4, 7], even though the AA derived according to Hannum et al's algorithm is linked closely to one CpG site, cg05575921, which had been identified as an epigenetic indicator of smoking exposure in previous EWASs [15, 24, 25]. Our study confirmed this locus and additionally identified 65 loci that were associated with both smoking and AA as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, none of the genomic regions that become either hypermethylated or hypomethylated with aging has been identified in smoking EWASs [4, 7], even though the AA derived according to Hannum et al's algorithm is linked closely to one CpG site, cg05575921, which had been identified as an epigenetic indicator of smoking exposure in previous EWASs [15, 24, 25]. Our study confirmed this locus and additionally identified 65 loci that were associated with both smoking and AA as well.…”
Section: Discussionmentioning
confidence: 99%
“…In more detail, we computed the mean β value ( μ c ) and standard deviation ( σ c ) across the never smokers of the given dataset, and then defined the SI as SI(s)=1ncnWcβcsμcσc where W c is +1(−1) if the smoking-associated CpG, c , is hypermethylated (hypomethylated) in smokers and where β c is the β value of this CpG in samples s [6]. We calculated the SI for each participant in both panels based on the validated AA associated loci, and then compared it with the single epigenetic smoking indicator cg05575921 ( AHRR ) used in the study by Beach et al, [15] and the SI estimated based on 1501 loci identified in the study by Teschendorff et al (Teschendorff SI) [6]. Mutual correlations of these indicators and AA were assessed by Spearman's correlation coefficients, and the associations of the smoking indicators with AA were assessed by mixed linear regression (Models 1 and 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly all 71 markers in their model lay within or near genes with known functions associated with age-related conditions, including Alzheimer’s disease, cancer, tissue degradation, DNA damage, and oxidative stress (Hannum et al 2013). Despite the fact that Hannum et al’s measure was developed using a White sample, their findings were recently replicated among a sample of Black Americans (Beach et al, in press). …”
Section: Introductionmentioning
confidence: 99%
“…One possibility is that the biological processes that determine differential rates of telomere shortening had already taken place in the subjects studied. The question of how best to precisely quantify biological aging is a focus of intensive research (Beach et al, 2015;Hertel et al, 2015). Future studies will develop therapeutic approaches aimed at decelerated loss of physiologic integrity earlier in the life course and extending healthy life span.…”
Section: Impact On Future Aging Researchmentioning
confidence: 99%